Penapisan Bakteri Endofit Akar Kedelai Secara in Planta untuk Mengendalikan Penyakit Pustul Bakteri - Trimurti Habazar; Zurai Resti; Yulmira Yanti; Jumsu Trisno; Afrika Diana (Jurnal Fitopatologi Indonesia, 2012)
Endophytic bacteria reside within plant hosts without causing disease symptoms. Bacterial endophytes promote plant growth and yield, suppress pathogens, may help to remove contaminants, solubilize phosphate, or contribute assimilable nitrogen to plants. The aim of this study were to obtain indigenous endophytic bacterial isolates, which have the ability to control bacterial pustule cause by Xanthomonas axonopodis pv. glycines and to increase growth and yield of soybean. The bacterial endophyte isolates were introduced as seed treatment (108 cfu/ml) and soil drench on 3 weeks old soybean seedling. Xanthomonas axonopodis pv. glycines were inoculated on one month old of soybean by pricking leaf methodes. The effect of bacterial endophyte on disease incidence, disease severity, plant growth and yield of soybean were evaluated. We have found two selected bacterial endophyte isolates from soybean’s rhizosphere (St4E1.1 and St1E1.1.), with the ability to control bacterial pustule and to increase growth and yield of soybean.Key words: bacterial endophyte, bacterial pustule, in planta technique, soybean